The GlobalEd Project: Learning in an Interdisciplinary Environment - Brown, Scott W.; Boyer, Mark A.; Niv-Solomon, Anat; Renfo, Wesley; Maneggia, Donalyn; Ioannou, Andri (My University, 2008)
Problem solving and decision making in the world is interdisciplinary in nature. Problems rarely exist within only one domain, nor do the implications and options for decision making fail to encompass interdisciplinary or multidisciplinary issues. The GlobalEd Project employs a technology rich environment for students to participate in a simulation of international relations and negotiation as a diplomat of a foreign country. The simulation consists of negotiations on a variety of international policy issues conducted by students from 10-15 schools through an Internet-based interface. This paper discusses the findings of an implementation of the simulation with middle school students. The discussion focuses on participants’ changes in academic knowledge and interests from participating in a simulation of international relations. The results are discussed in terms of the current literature on problem-based learning (PBL).
Keywords: E-learning; Higher education; AACE